A new delineation for Oreocharis incorporating an additional ten genera of Chinese Gesneriaceae - Moller, M.; Middleton, D.; Nishii, K.; Wei, Y. G.; Sontag, S.; Weber, A. (Phytotaxa, 2011)
Based on molecular data and a morphological evaluation, evidence is provided that the species of eleven, mostly small-sized and monotypic genera of Chinese Gesneriaceae (Ancylostemon, Bournea, Briggsia s.str., Dayaoshania, Deinocheilos, Isometrum, Opithandra, Oreocharis, Paraisometrum, Thamnocharis, Tremacron) form a highly-supported group in which the species interrelationships run across traditional generic boundaries. The data confirm previous doubts on the naturalness of some of these genera and, after a detailed discussion of the particular genera, the conclusion is reached that the whole group is best regarded as a single genus, Oreocharis, which is thus expanded to comprise over 80 species. A list of the species is given and the necessary transfers are made. The new delimitation provides a framework for studying the species relationships and working out an infrageneric classification. Oreocharis provides an excellent example of a major monophyletic group that has experienced a rapid radiation early in its evolution and shows manifold convergences in floral characters (corolla form and coloration, fertility of stamens, anther shape and dehiscence mode), apparently reflecting different pollination strategies, but has little variation in vegetative habit and fruit structure.